Use of sunscreen in soybean cultivation: A scientific note (Research, Society and Development, 2025)
This study aimed to understand the development and productivity of soybeans after foliar sunscreen application. The experimental design was a completely randomized block design, with two sunscreens: Surround®, Sundown®, and absence (Control), resulting in three treatments. Four plots were used per treatment, totaling 16 plots. The plots were 2.7 m wide and 8.0 m long, totaling 21.6 m2. The Surround® and Sundown® sunscreens showed similar responses for leaf number, pod number, and grain yield in soybean crops. The use of sunscreen may be an alternative to mitigate light stress in soybean crops. Further studies are needed to understand the physiological and developmental responses of soybeans grown after sunscreen application.